2010
DOI: 10.1080/00103620903426931
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Soil Physical Properties in a Cleared Forestland Continuously Cultivated for Seven Years in Eastern Nsukka, Nigeria

Abstract: In this study, soil physical properties were evaluated in the top 40 cm of cleared forestland that had been subjected to continuous cultivation for 7 years to ascertain selected crop or crop combinations that influenced the soil physical properties the most. There was no significant effect of crop treatment on particle-size distributions over 6 years of cultivation. In year 7, clay values were significantly (p 5 0.05) greater in plots grown with solely cassava (SC) and solely maize (SM) than in the plots grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
(8 reference statements)
4
6
0
Order By: Relevance
“…Research has shown that topsoils usually show a higher sand content than subsoils (Nartey et al, 1997;Usowicz et al, 2004), and the present results suggest that this is due mainly to coarse sand and not fine sand ( Table 2). The silt content showed no appreciable change with depth, and this agrees with other reports from the area (Igwe, 2005;Asadu et al, 2010). For the clay content, the soil depth zone ranked closely next to location.…”
Section: Rwsupporting
confidence: 90%
See 2 more Smart Citations
“…Research has shown that topsoils usually show a higher sand content than subsoils (Nartey et al, 1997;Usowicz et al, 2004), and the present results suggest that this is due mainly to coarse sand and not fine sand ( Table 2). The silt content showed no appreciable change with depth, and this agrees with other reports from the area (Igwe, 2005;Asadu et al, 2010). For the clay content, the soil depth zone ranked closely next to location.…”
Section: Rwsupporting
confidence: 90%
“…This is possibly due to pronounced clay illuviation in these Ultisols, especially with their coarse texture. Asadu et al (2010) reported a similar observation in cultivated plots in the Nsukka site of the present study. It appears thus that sampling at a soil-depth interval of 30 cm could permit the expression of clay eluviation/illuviation phenomenon in these soils.…”
Section: Rwsupporting
confidence: 86%
See 1 more Smart Citation
“…It lies within the latitude 6º 52´ N and longitude 7º 23´ E in the Savannah zone of Southeastern Nigeria with an elevation of 447.2 m above sea level [43]. The climate of the area is characterized by an average annual rainfall of about 1550 mm and average temperatures (minimum and maximum) of 22 ˚C and 30 ˚C respectively while the average relative humidity is 60% [12]. Soils in this area are generally derived from the residua of False-bedded Sand-stone or Upper-coal Measure Formation as a result of disintegration of the rocks [10].…”
Section: Methodsmentioning
confidence: 99%
“…More details on this study can be obtained from the following journal publications; Dixon and Asadu 2001;Asadu and Dixon 2005;Asadu et al 2010;Asadu et al 2013 andAsadu et al 2014. The summary may be given as follows: In 1998, after clearing the forest and before embarking on the establishment of the trials, soil samples were collected at random to assess the variability in the soil properties in order to ascribe subsequent variations to treatments applied.…”
Section: Background Of the Studymentioning
confidence: 99%